Does the EU Eco-design for Sustainable Product Regulation Address Premature Obsolescence? A Systemic Perspective on Barriers to Longer Product Lifetime - Gulati, Bhavesh; Dillenseger, Laëtitia; Cresci, Irene; Luzzati, Tommaso (Proceedings of the 6th Product Lifetimes and the Environment Conference (PLATE2025), 2025)
Premature obsolescence has significant environmental and socioeconomic impacts. Extending the lifetime of products is a key aim of the Eco-design for Sustainable Product Regulation (ESPR), recently introduced by the European Commission. Several barriers to achieving longer product lifetime have been identified in the literature. By examining the systemic interplay among these barriers and forms of premature obsolescence, we develop a framework to analyse the potential effectiveness of ESPR. Our findings reveal that these barriers are interconnected and mutually reinforcing, confirming the need for public policies that address these interactions and reduce premature obsolescence. Moreover, while the ESPR successfully addresses technical and economic challenges related to product lifetime extension, it remains limited in tackling symbolic obsolescence and ingrained societal consumption patterns.